Outcome of Unilateral Bladder Neck Incision In Comparison to Bilateral Incision in Case of Primary Bladder Neck Obstruction - Alam, Md Nabid; Debnath, Ripan; Ahmed, Maruf; Islam, Muhammad Serajul; Saiful Hossain, Tohid Mohammad; Alam, SM Mahbub; Rahman, Md Mostafizur (Bangladesh Journal of Urology, 2022)
Background: Primary bladder neck obstruction is not uncommon in middle aged men. Patients with primary bladder neck obstruction usually present with voiding and storage symptoms. They are evaluated by history, physical examination, investigations and confirmed by urodynamic study. There are different modalities of treatment. It varies according to age, sex and associated conditions. If medical treatment failed, they are treated with unilateral or bilateral bladder neck incisions. Among them, per and postoperative outcome like operation time, hospital stay, voiding time, PVR, Qmax and retrograde ejaculation were assessed in both the group. Objectives: The purpose of this study was to compare the operation time, postoperative hospital stay, PVR, Qmax, voiding time and retrograde ejaculation between two groups who underwent unilateral or bilateral bladder neck incision due to primary bladder neck obstruction. Material and methods: This quasi experimental study was carried out in the department of urology, Dhaka Medical College Hospital, Dhaka, from July 2013 to June 2015. Male patients with lower urinary tract symptoms due to primary bladder neck obstruction were the study population. Sixty patients were selected from Urology OPD as sample according to inclusion and exclusion criteria. Then, they were divided into two groups purposively, designated as group I and group II for unilateral and bilateral bladder neck incision respectively to see the per and postoperative outcome like operating time, hospital stay, voiding time, PVR, Qmax and retrograde ejaculation Results: Total 60 patients were recruited in this study of which 30 patients were in group I and the rest of 30 patients were in group II. The mean age with a SD was 28.33 ± 5.33 years and 28.20±5.49 years in group I and group II respectively (p>0.05). In group I, the mean ± SD of operative time was 19.9±3.26 min within a range 15-25 min. In group II, the mean ± SD of operative time was 27.16 ±2.65 min within a range 20-30 min (p<0.05).In group I mean (SD) hospital stay was 2.10 ± 0.30 day, in group II it was 2.40 ± 0.56 day Bangladesh J. Urol. 2021; 24(1): 46-52